Automated Electrophysiology Makes the Pace for Cardiac Ion Channel Safety Screening - Moeller, Clemens; Witchel, Harry (Frontiers in Pharmacology, 2011)
The field of automated patch-clamp electrophysiology has emerged from the tension between the pharmaceutical industry’s need for high-throughput compound screening versus its need to be conservative due to regulatory requirements. On the one hand, hERG channel screening was increasingly requested for new chemical entities, as the correlation between blockade of the ion channel coded by hERG and Torsades de Pointes cardiac arrhythmia gained increasing attention. On the other hand, manual patch-clamping, typically quoted as the “gold-standard” for understanding ion channel function and modulation, was far too slow (and, consequently, too expensive) for keeping pace with the numbers of compounds submitted for hERG channel investigations from pharmaceutical R&D departments. In consequence it became more common for some pharmaceutical companies to outsource safety pharmacological investigations, with a focus on hERG channel interactions. This outsourcing has allowed those pharmaceutical companies to build up operational flexibility and greater independence from internal resources, and allowed them to obtain access to the latest technological developments that emerged in automated patch-clamp electrophysiology – much of which arose in specialized biotech companies. Assays for nearly all major cardiac ion channels are now available by automated patch-clamping using heterologous expression systems, and recently, automated action potential recordings from stem-cell derived cardiomyocytes have been demonstrated. Today, most of the large pharmaceutical companies have acquired automated electrophysiology robots and have established various automated cardiac ion channel safety screening assays on these, in addition to outsourcing parts of their needs for safety screening.